The effect of anomaly detection accurancy in varying the angular resolution of sonar using repetitive observation strategy - Mohd Nurul Al-Hafiz , Sha' abani; Muhammad Fahmi , Miskon (2011)
This paper presents the feasibility study of implementing Repetitive Observation Strategy (ROS) using a sonar sensor array. ROS is a method that collects observation data taken from different observer positions for anomaly detection purposes. This strategy had never been implemented using sonar sensor. The study is conducted using simulation in MATLAB. The simulation is run by varying the angular resolution of the sonar sensor array which covered 180 degrees. The performance of anomaly detection is analyzed using Receiver Operating Characteristic (ROC) curve. Result shows that the performance of anomaly detection decrease as the angular resolution of sensor increases.